Incorporating the United Nations protocol on trafficking in persons in the Malaysian legal framework - Mokhtar, Khairil Azmin; Ab Hamid, Zuraini (IIUM Press, 2016)
The international framework of anti-human trafficking has become the main guiding framework for countries around the globe in combating the crime. The issue of human trafficking was brought to global attention mainly by the Protocol to Prevent, Suppress and Punish Trafficking in Persons especially Women and Children. The UN Protocol provides a standard approach to state parties in combating human trafficking. The approach is known as “3Ps” model which aim to prevent the crime, to protect the victim and to prosecute the perpetrator. In spite of the creation of AntiTrafficking National Action Plan (NAP) in 2012 and the passing of the Anti-Trafficking in Persons and Anti-Smuggling of Migrants Act 2007 (ATIPSOM 2007) by the Malaysian government in the US Department of State Trafficking in Persons Report 2014 (TIP) it is stated that “3Ps” approach is lacking in the Malaysian legal framework. This paper analyses whether Malaysia’s legal response through its Anti Trafficking in Persons and Smuggling of Migrants Act 2007 and other relevant legislation are in compliance with the Protocol. In this study it is found that there are many aspects of rights and protection still wanting within the legal framework of human trafficking in the country. Reformation of Malaysia’s legal framework in combating human trafficking is much needed to ensure its compliance with the international framework and in order for the local enforcement agencies to be more successful in combating the crime.